Short-term social modulation of 11-ketotestosterone urinary levels in males of cichlid fish Oreochromis mossambicus during male-femaleInteraction - Borges, R. (2014)
After 48 hours social isolation, male individuals of Oreochromis mossambicus wera allowed to interact with a conspecifif female in the same aquarium during a period of six hours.